Potential imbalanced differences of grain production in the sustainable development of county cities—a case study of Jiangsu Province - Li, Xiaoming; Xu, Jinhai; Guo, Zheng; Li, Xin; Jin, Tao; Lu, Jieqiong; Li, Tianrui (Frontiers in Sustainable Food Systems, 2024)
Introduction Grain production at the regional level is related to the strategic development orientation of the country as a whole, and maintaining the stability of grain production is of great importance in ensuring the sustainable development of the food system. Studying the potential imbalance differences resulting from the spatial and temporal development of grain production and its driving factors will help to reduce the contradiction between the rapid development of the urban economy and the inappropriate use of arable land resources, thus coordinating regional agricultural development and further clarifying the direction and focus of future food security construction work. Methods This study focuses on the potential imbalance differences based on spatial and temporal development of grain production in Jiangsu Province during the period 1990–2020, and explores the spatial and temporal patterns and driving mechanisms of grain production spatial autocorrelation model and spatial error model are applied to analysis the spatial and temporal characteristics of grain production and security in Jiangsu Province and their influencing factors. Results The results are as follows: (1) The total amount of food in Jiangsu Province increased by 17.36% during the 30-year period, but the growth rate was lower than the national average. (2) Regional differences are significant, with a significant decline in grain production in southern Jiangsu and growth in northern and central Jiangsu. (3) The center of gravity for grain production has shifted to northern Jiangsu. (4) Grain production is significantly correlated with socio-economic factors such as per capita ownership, sown area, irrigated area, and cultivated area. Discussion To ensure the sustainability of food production in the future, attention should be paid to the risk of imbalance in regional food production, coordination of socio-economic factors, promotion of efficient agricultural production, improvement of the relevant policy system and optimization of the food production system.